The monitoring mechanism of the intellectual technologies commercial potential - Kosenko, O. (University of Engineering and Economics, Poland, 2015)
The theoretical and methodological foundations of intellectual technologies monitoring that are based on intellectual property are considered in the article. We prove that the evaluation of intellectual technologies market opportunities by the enterprise, the state of their target market, market changes on it to determine the position of the enterprise relatively goods analogs and substitute goods and identification of possible prospects and areas of intellectual development can be done very effectively using the principles and methods of economic monitoring. Methodical provision of monitoring commercial potential of intellectual property using the function of tangential economic effect is elaborated.
Keywords: monitoring; commercial potential; smart technology; economic impact; transfer; commercialization